College Women and Fertility Values - Westoff, Charles F. (Book collections on Project MUSE., 2016)
Has the college experience of women been an influence on the number of children desired and the number and spacing of their children? Do women come to college with their attitudes and values in this regard already formed? This study of 15,000 women, freshmen and seniors in 45 American colleges and universities, both secular and nonsecular, attempts to answer this question and to determine how such characteristics as religious preference, career intentions, and the number of children in her own family influence a woman's fertility values. Attention is paid to an earlier finding that Catholic college graduates have higher fertility than Catholic high school graduates, although higher education is usually associated with lower fertility. Originally published in 1967. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.